Epigenetics as an answer to Darwin’s “special difficulty” - Herb, Brian R. (Frontiers in Genetics, 2014)
Epigenetic modifications produce distinct phenotypes from the same genome through genome-wide transcriptional control. Recently, DNA methylation in honeybees and histone modifications in ants were found to assist the formation of caste phenotypes during development and adulthood. This insight allows us to revisit one of Darwin’s greatest challenges to his natural selection theory; the derivation of multiple forms of sterile workers within eusocial species. Differential feeding of larvae creates two distinct developmental paths between queens and workers, with workers further refined by pheromone cues. Flexible epigenetic control provides a mechanism to interpret the milieu of social cues that create distinct worker sub-caste phenotypes. Recent findings suggest a distinct use for DNA methylation before and after adult emergence. Further, a comparison of genes that are differentially methylated and transcriptionally altered upon pheromone signaling suggests that epigenetics can play a key role in mediating pheromone signals to derive sub-caste phenotypes. Epigenetic modifications may provide a molecular mechanism to Darwin’s ‘special difficulty’ and explain the emergence of multiple sub-phenotypes among sterile individuals.